The seven myths of encrypted traffic scanning. Issue 7 (July 2021) - Lueck, Marc
Abstract : The belief that encrypted traffic is secure in a world where businesses rely increasingly on the Internet is a widespread misunderstanding that is as persistent as it is misguided. While TLS encryption was developed to protect traffic from prying eyes, adversaries have unfortunately begun to leverage this traffic to hide their attacks, turning the use of encryption into a potential threat.